Choosing to lead : understanding Congressional foreign policy entrepreneurs - Carter, Ralph G. (e-Duke books scholarly collection., 2009)
Assesses Congress's role in U.S. foreign policy making, focusing on congressional foreign policy "entrepreneurs" who try to either change or create new foreign policies without specific prompting from the executive branch.